Contamination of argon x-ray spectra by tungsten and other elements commonly found in tokamaks. (7th May 2021) - Rice, J E; Gu, M; Cao, N M; Hughes, J W; Reinke, M L; Sertoli, M; Vezinet, D
Abstract: Emission lines which appear in the spectral ranges of ground state transitions from n = 2 levels in He- and H-like argon ions are discussed. X-ray transitions from elements commonly found in tokamaks (tungsten, molybdenum, iron and sulphur) which radiate in the wavelength range from 3700–4000 mÅ are identified by comparison with atomic structure calculations. Individual lines from tungsten charge states in the vicinity of Zn-like W 44+ are documented, along with B-like Mo 37+ . The behaviour of line ratios as a function of electron temperature is examined, in support of the identifications.